Weight gain associated with insulin detemir vs insulin glargine in clinical practice: A retrospective longitudinal cohort study. (23rd December 2020) - Wadsworth, Thomas G; Carr, Glenda G; Madaras-Kelly, Karl; Remington, Richard; Bell, Justin
Abstract: Purpose: In comparative randomized studies, use of insulin detemir has been consistently demonstrated to be associated with less weight gain than the industry standard, insulin glargine. However, the magnitude of the relative reduction in weight gain with use of insulin determir vs insulin glargine in regulatory studies (reported values ranged from 0.77 kg to 3.6 kg) may not be generalizable to patients in real-world practice conditions. A study was conducted to substantiate detemir's purported weight-sparing advantage over insulin glargine in newly treated patients with type 2 diabetes mellitus under the conditions found in a clinical practice setting. Methods: A retrospective longitudinal cohort study design was applied in reviewing electronic medical records to identify insulin-naive, overweight patients with type 2 diabetes who received insulin detemir or insulin glargine therapy continued for up to 1 year. Patient weights at baseline and at each subsequent clinic visit after treatment initiation were identified. The primary outcome was the maximum weight increase from baseline after exposure to insulin detemir or glargine. The difference-in-differences (DiD) mean total body weight change was tested by analysis of covariance (ANCOVA). Results: One hundred nine patient records (56 of patients who received insulin glargine and 53 of patients who received insulin detemir) met study criteria and underwent full abstraction. The covariate-adjusted estimated mean change in body weight associated with use of insulin detemir vs insulin glargine was –1.5 kg (95% CI, –2.89 to –0.12 kg; P = 0.04). Conclusion: The mean weight gain associated with detemir use was significantly less than the mean weight change observed with glargine use. The magnitude of weight change was consistent with that demonstrated in randomized controlled trials. These results further substantiate detemir's purported comparative weight-sparing properties under conditions found in a real-world practice setting.